Characterization of the Gut Microbiome in Egyptian Patients with Schizophrenia and Bipolar Disorder - Khalel, Rana Salah Mohamed Foaud (AUC Knowledge Fountain, 2026)
Recent evidence highlights the gut microbiome as a critical modulator of brain function through the gut–brain axis, with growing associations between microbial dysbiosis and major psychiatric disorders, including Schizophrenia (SCZ) and Bipolar disorder (BD). Despite substantial global advances in this field, the gut microbial landscape of psychiatric populations in Egypt and the wider Middle East remains largely unexplored. This study aimed to identify diagnostic taxonomic and predicted functional microbial signatures in an underrepresented cohort of Egyptian patients with SCZ and BD. Fecal samples were collected from 127 participants (54 SCZ, 53 BD, and 20 healthy controls), followed by DNA extraction and 16S sequencing. Microbial alpha/beta diversities, and taxonomic composition were assessed, and differential abundance analyses were conducted to identify disorder-associated taxa. Predictive functional profiling was performed to investigate alterations in microbial metabolic pathways relevant to psychiatric pathophysiology. The results demonstrated significant alterations in gut microbiome structure in both Schizophrenia and Bipolar disorder compared with healthy controls, including disorder-specific differences in microbial composition and beta diversity. Multiple taxa involved in inflammatory regulation, short-chain fatty acid production, and metabolic signaling were differentially abundant across diagnostic groups. Predicted functional analyses revealed disruptions in pathways related to amino acid metabolism, neurotransmitter-associated processes, and immune modulation, supporting a role for microbial functional dysregulation in psychiatric disease mechanisms. Notably, the Schizophrenia-associated microbiome exhibited significant enrichment of dopamine degradation pathways, suggesting a potential metabolic link to the disorder’s established neurochemical abnormalities. To our knowledge, this study provides the first comprehensive characterization of the gut microbiome in Egyptian patients with Schizophrenia and Bipolar disorder. The findings reveal both shared and disorder-specific dysbiotic signatures and emphasize the importance of population-specific microbiome research. By integrating regionally representative microbial data with broader global evidence, this work contributes to the development of more personalized neuropsychiatric diagnostics and therapeutics and establishes a foundation for the future application of microbial biomarkers in deep learning–based diagnostic prediction models.